Diversity, equity & inclusion for trainers - Morukian, Maria (ATD Press, 2022)
Make DEI Training Foundational in Your Organization. When done well, diversity, equity, and inclusion (DEI) training creates space for courageous conversations that acknowledge hard truths around systemic inequities and explores topics that touch on people's vulnerabilities in all facets of their lives. For those of you who do this work, there has not been a clear path to follow for making progress. As a DEI trainer, you have forged your own way and learned as you went. With Diversity, Equity, and Inclusion for Trainers: Fostering DEI in the Workplace, the need for DEI trainers to go at it alone comes to an end. Expert facilitator Maria Morukian provides the guidance you need to develop the knowledge and skills required for DEI training. Morukian covers the historical underpinnings and rationale for DEI work; takes you through the process of organizational assessment, design, and delivery; and offers strategies for embedding DEI and promoting sustainability through collaborative practices and dialogues, allowing you to develop and understand your own identity lenses and biases. Reflection questions and worksheets are included in every chapter.